2011
DOI: 10.3892/ijmm.2011.639
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary identification of potential PDZ-domain proteins downstream of ephrin B2 during osteoclast differentiation of RAW264.7 cells

Abstract: Abstract. The EphB4 receptor and ephrin B2 ligand were recently reported to influence the coupling between osteoclasts and osteoblasts in bone biology, but their downstream signaling pathways remain unclear. This study focuses on the preliminary identification of downstream PDZ-domain proteins involved in EphB4/ephrin B2 reverse signaling in osteoclasts. Similarly to primary osteoclast precursors isolated from the bone, we observed that the RAW264.7 cell line, a mouse monocyte/macrophage cell line that is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Intracellular signaling by which ephrins regulate osteoclast development and activity also utilizes non-ephrin molecular pathways. In the RAW264.7 pre-osteoclast cell line, Dishevelled2 (Dvl2) co-precipitation with efnB2 was increased by RANKL treatment and reduced by EphB4 treatment, indicating that Dvl2 could be a downstream effector of reverse signaling that associates with efnB2 and mediates cell migration [59] . It has been also recently shown that EphA4 regulates osteoclast activity by modulating β3-integrin functions [47] , presumably by promoting attachment to the extracellular matrix.…”
Section: Efn-eph Intracellular Signalingmentioning
confidence: 99%
“…Intracellular signaling by which ephrins regulate osteoclast development and activity also utilizes non-ephrin molecular pathways. In the RAW264.7 pre-osteoclast cell line, Dishevelled2 (Dvl2) co-precipitation with efnB2 was increased by RANKL treatment and reduced by EphB4 treatment, indicating that Dvl2 could be a downstream effector of reverse signaling that associates with efnB2 and mediates cell migration [59] . It has been also recently shown that EphA4 regulates osteoclast activity by modulating β3-integrin functions [47] , presumably by promoting attachment to the extracellular matrix.…”
Section: Efn-eph Intracellular Signalingmentioning
confidence: 99%
“…However, the exact phosphorylation sites of EphrinB2 remained obscure. The PDZ-dependent signaling was activated by binding proteins with PDZ domain to the PDZ motif, such as PDZ-RGS3 [16] and Dvl2 [17, 18], playing an important role in EphrinB2-mediated embryonic development and angiogenesis despite of the unclarified downstream efforts (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Dishevelled (Dsh) is a key molecule in Wnt signalling and is also known to be a major player in the Wnt/PCP pathway required for proper neural crest cell migration 18 , 39 . Previous studies demonstrated that Dsh interacts with the C-terminal PDZ-binding motif of ephrinB ligands 40 43 , which is also the motif required for the interaction with TBC1d24 (Fig. 1d ).…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, our data support a mechanistic model for how ephrinB2 may regulate CIL in CNC cells via TBC1d24. TBC1d24 interacts with ephrinB2 through the known association of ephrinB2 and Dsh 40 43 , as indicated in Fig. 2 .…”
Section: Discussionmentioning
confidence: 84%